Pengaruh Pengajaran dan Persekutuan Terhadap Tingkat Pertumbuhan Rohani Anak dan Remaja - Helen Farida Latif (Sekolah Tinggi Teologi Torsina Surakarta, 2017)
Evangelism to the lost souls is very important for the church to do, and no less important that the church should do, that is, to increase the spiritual growth of the church. In order for the spirituality of the church, including children and youth to experience growth until full maturity according to the will of God is necessary for continuous coaching through teaching and fellowship. In this research, the authors identify that the teaching and the fellowship have a very significant influence on the spiritual growth of children and youth, especially in the Gereja Sungai Yordan Keluarga Allah Kutabumi, Tangerang. This research is to determine the influencing of the teaching and the fellowship to the spiritual growth of children and adolescents. The research was conducted by analyzing data on the presence of children and adolescents in the Bible teaching classes and the fellowship and their spiritual growth based scores on Ephesians 4:13-15 and Acts 2:41-47 using scale interval